A escrita de estórias por crianças: as implicações pedagógicas do uso de um registro lingüístico - Rego, Lucia Browne (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2016)
This paper examines the story writing ability of first graders who attended the same pre-school classes in private schools in Recife. On the basics of a socio-functional perspective of language and of language learning our impirical analysis suggests that: a. The differences in the children’s performances indicate thet there are language acquisition processes which need to be further investigated. b. A better knowledge of these processes and of their developmental contexts might contribute to improve language teaching in pre-school years.